2006
DOI: 10.1165/rcmb.2005-0277oc
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin in the Fibroproliferative Response to Acute Lung Injury

Abstract: Resolution of alveolar epithelial/capillary membrane damage after acute lung injury requires coordinated and effective tissue repair to reestablish a functional alveolar epithelial/capillary membrane barrier. We hypothesized that signaling pathways important in lung alveolar bud ontogeny are activated in the recovery and remodeling phases after profound oxidant stress lung injury in a murine model. To test this, we characterized the expression of noncanonical ␤-catenin pathway proteins E-cadherin, integrin-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 52 publications
3
59
2
Order By: Relevance
“…Cyclin D1 is a cell cycle regulatory molecule that is active in G1 phase transition and functions as an important mitogenic regulator (26). Increased cyclin D1 expression is linked to acute and chronic lung injuries induced by inflammatory agents, and it is postulated to contribute to interstitial cell proliferation and fibrosis formation (27,28). Collagen 1a1 and fibronectin are the main components of ECM that participate in tissue and vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 is a cell cycle regulatory molecule that is active in G1 phase transition and functions as an important mitogenic regulator (26). Increased cyclin D1 expression is linked to acute and chronic lung injuries induced by inflammatory agents, and it is postulated to contribute to interstitial cell proliferation and fibrosis formation (27,28). Collagen 1a1 and fibronectin are the main components of ECM that participate in tissue and vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…17 Cyclin D1 immunohistochemistry and ␤-catenin immunofluorescence staining (both from Cell Signaling Technology, Danvers, MA) were performed on paraffin-embedded lung tissue. 18,19 Briefly, lung tissue sections were deparaffinized and rehydrated. Antigen retrieval was performed by boiling slides in sodium citrate buffer (pH 6.0) for 10 minutes.…”
Section: Lung Histology and Immunohistochemistrymentioning
confidence: 99%
“…Pulmonary fibrotic lesions frequently exhibit a heterogeneous increase in vessel density, and an extant and important question is whether the release of angiogenic factors enables the development of fibrosis or, conversely, if it is a compensatory mechanism to prevent more severe fibrotic changes (3,5,6). Detection of VEGF protein by Western Blot analysis in whole-lung lysates revealed markedly elevated VEGF levels after intraperitoneal bleomycin treatment (i.p.)…”
Section: Vegf-a Levels and Endothelial Numbers Are Significantly Redumentioning
confidence: 99%
“…Among myeloid cells that infiltrate the lung during the inflammatory phase of pulmonary fibrosis, macrophages represent a major population that is also known for its ability to release large amounts of VEGF (2). The significance of angiogenesis, particularly expression of the angiogenic factor VEGF, in pulmonary fibrosis is a matter of controversy (3)(4)(5), however. In lung tissue, recent work has shown that delivery of VEGF can aggravate pulmonary fibrosis but alleviate pulmonary hypertension, highlighting the complexity of its role (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation